Pengaruh Kepemimpinan Transaksional, Motivasi Kerja dan Employee Engagement terhadap Kepuasan Kerja Karyawan (Studi pada Happy Day Organizer) - Andalas, Yasir; Marpaung, Nicholas (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This research aims to analyze the influence of transactional leadership, work motivation and employee engagement on employee job satisfaction. The influence of transactional leadership, work motivation and employee engagement will be analyzed partially and simultaneously on employee job satisfaction. The form of research used in this research is quantitative research with an associative approach. Sampling was carried out using a saturated sampling technique with 33 respondents as samples. Primary data used in this research was obtained by distributing questionnaires directly, while secondary data was obtained through literature study. The data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression test, and hypothesis test. The results of the research conducted show that the variables transactional leadership (X1), work motivation (X2) and employee engagement (X3) have a significant effect on employee job satisfaction and all independent variables simultaneously (simultaneously) influence employee performance.